The challenge of change : military institutions and new realities, 1918-1941 - Winton, Harold R., 1942-; Mets, David R. (Studies in war, society, and the military., 2000)
The Challenge of Change examines how military institutions attempted to meet the demands of the new strategic, political, and technological realities of the turbulent era between the First and Second World Wars. The contributors chose France, Germany, Great Britain, the Soviet Union, and the United States as focus countries because their military institutions endeavored to develop both the material capacity and the conceptual framework for the conduct of modern industrialized warfare on a continental scale.